2009
DOI: 10.1111/j.1528-1167.2009.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for imaging infants and children with recent‐onset epilepsy

Abstract: SUMMARYThe International League Against Epilepsy (ILAE) Subcommittee for Pediatric Neuroimaging examined the usefulness of, and indications for, neuroimaging in the evaluation of children with newly diagnosed epilepsy. The retrospective and prospective published series with n ‡30 utilizing computed tomography (CT) and magnetic resonance imaging (MRI) (1.5 T) that evaluated children with new-onset seizure(s) were reviewed. Nearly 50% of individual imaging studies in children with localization-related new-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
182
1
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(212 citation statements)
references
References 37 publications
11
182
1
18
Order By: Relevance
“…In one study reported by Ibrahim et al, for example, the time from seizure onset to tumour diagnosis among ten children presenting with seizures ranged from two weeks to two years, averaging six months [37]. A wide range of opinions and practices exist regarding how aggressive to pursue diagnostic imaging in children presenting with seizures [36,41,51,79,80,100,[127][128][129][130][131][132][133]. For example, in one series of eighteen patients between the ages of 1 month and 13 years who presented with seizures and were discovered to have DNETs between January 1992 and December 2004, the preoperative evaluation included magnetic resonance (MR) imaging and interictal scalp electro-encephalography (EEG) in all patients, but functional MR imaging also was performed in eight patients, video monitoring with scalp EEG during seizures in 12 patients, interictal single-photon emission computerized tomography (SPECT) scanning in one patient, and ictal SPECT scanning in two patients [132].…”
Section: How Seizures Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study reported by Ibrahim et al, for example, the time from seizure onset to tumour diagnosis among ten children presenting with seizures ranged from two weeks to two years, averaging six months [37]. A wide range of opinions and practices exist regarding how aggressive to pursue diagnostic imaging in children presenting with seizures [36,41,51,79,80,100,[127][128][129][130][131][132][133]. For example, in one series of eighteen patients between the ages of 1 month and 13 years who presented with seizures and were discovered to have DNETs between January 1992 and December 2004, the preoperative evaluation included magnetic resonance (MR) imaging and interictal scalp electro-encephalography (EEG) in all patients, but functional MR imaging also was performed in eight patients, video monitoring with scalp EEG during seizures in 12 patients, interictal single-photon emission computerized tomography (SPECT) scanning in one patient, and ictal SPECT scanning in two patients [132].…”
Section: How Seizures Presentmentioning
confidence: 99%
“…Seizures even increase a paediatric survivor's risk of suicide into adulthood [31]. In addition, there is a subset of children, up to 50% [32], whose low-grade brain cancer presents as seizures [26,[32][33][34][35][36][37][38][39][40][41][42]. Though the vast majority of epileptogenic tumours are supratentorial, some are not, especially among children in whom infratentorial tumours generally comprise the majority [43,44], and in less typical locations like the thalamus and hypothalamus [38,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular enlargement, especially mild, was also fairly frequent (12% of total sample). Structural neuroimaging is recommended for all children with recently diagnosed localization-related or generalized epilepsy who do not have the clinical and electrographic features characteristic of classical idiopathic focal or generalized epilepsy (these include benign epilepsy with centrotemporal spikes, childhood absence epilepsy, juvenile absence epilepsy, and juvenile myoclonic epilepsy) 16,[31][32][33] . However, this series shows how structural abnormalities judged to be etiologically related to the seizure conditions have been found in idiopathic focal or generalized epilepsy, which are consistent with other published data 23,34,35 .…”
Section: Whole Samplementioning
confidence: 99%
“…(15,16) Imaging helps in establishing aetiology, providing prognostic information and aids the treatment in children, particularly those with newly diagnosed epilepsy. (17) Developmental malformations are the most common abnormalities detected in children and adolescents by imaging. (18,19) Malformations of Cortical Development (MCD) are a heterogeneous group of disorders characterised by an abnormal architecture of the cerebral cortex and the most common cause of partial seizures as well as intractable epilepsy in children.…”
mentioning
confidence: 99%
“…(18,19) Malformations of Cortical Development (MCD) are a heterogeneous group of disorders characterised by an abnormal architecture of the cerebral cortex and the most common cause of partial seizures as well as intractable epilepsy in children. (17) Focal Cortical Dysplasia (FCD) is characterised by heterogeneous lesions exhibiting abnormal neuronal or glial cells within a localised region of cerebral cortex. Out of the MCDs, they may escape detection by a routine MRI and sometimes even with special techniques.…”
mentioning
confidence: 99%